2008
DOI: 10.1016/j.mce.2007.12.010
|View full text |Cite
|
Sign up to set email alerts
|

In vitro testing of new somatostatin analogs on pituitary tumor cells

Abstract: It has been indeed demonstrated that native SRIF inhibits secretion and proliferation of both normal and neoplasic pituitary cells by inducing several intracellular pathways, depending on receptor subtype and target tissue (Ferjoux et al. 2000). Therefore, many studies subsequently explored SSTR subtype expression in pituitary adenomas, demonstrating that SSTR2 is the most frequently expressed subtype (Panetta and Patel, 1995 A c c e p t e d M a n u s c r i p t 3 SSTR 2 and 5 mRNA were always expressed, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The fact that sst2 agonists, and not high concentration SST, could block basal GH release may be related to the fact that SST binds to all sst subtypes, where each is known to differentially couple to G‐proteins (5) and upon ligand binding can form homo‐ or heterodimers that can in turn modify their association with intracellular signals (28,29). In support of the results obtained in the present study, studies using SST receptor specific agonists/antagonists in GH‐producing cell lines, primary pituitary cultures (pigs, chickens, rats) and/or human pituitary GH‐producing adenomas cultures have revealed that only sst2 consistently confers the inhibitory actions of SST on GH release, whereas activation of the other SST receptor subtypes is variable depending on the concentration of agonist supplied and the model tested (1,10,12,14,30–32). It has also been shown, using nonprimate models, that sst2‐mediated inhibition of GH release requires intact AC activity and is associated with inhibition of cAMP accumulation and voltage‐gated Ca 2+ channels, and/or stimulation of membrane K + channels (1,7,10,12,14).…”
Section: Discussionsupporting
confidence: 88%
“…The fact that sst2 agonists, and not high concentration SST, could block basal GH release may be related to the fact that SST binds to all sst subtypes, where each is known to differentially couple to G‐proteins (5) and upon ligand binding can form homo‐ or heterodimers that can in turn modify their association with intracellular signals (28,29). In support of the results obtained in the present study, studies using SST receptor specific agonists/antagonists in GH‐producing cell lines, primary pituitary cultures (pigs, chickens, rats) and/or human pituitary GH‐producing adenomas cultures have revealed that only sst2 consistently confers the inhibitory actions of SST on GH release, whereas activation of the other SST receptor subtypes is variable depending on the concentration of agonist supplied and the model tested (1,10,12,14,30–32). It has also been shown, using nonprimate models, that sst2‐mediated inhibition of GH release requires intact AC activity and is associated with inhibition of cAMP accumulation and voltage‐gated Ca 2+ channels, and/or stimulation of membrane K + channels (1,7,10,12,14).…”
Section: Discussionsupporting
confidence: 88%
“…Octreotide is a clinically used somatostatin analogue that binds primarily to SSTR2 and to a lesser extent to SSTR5, BIM-23120 exhibits a very specific affinity to SSTR2, whereas SOM-230 is a multi-somatostatin receptor ligand with high affinity for SSTR1, SSTR2, SSTR3 and SSTR5 42 53 54 . These somatostatin analogues have been previously shown to inhibit GH secretion in primary cultures of human GH-secreting adenomas (for reviews, see 55 56 ). In keeping with these observations, all somatostatin analogues cause a marked decrease in GH secretion in GC tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 The α-subunit measurements have been used to study the effects of experimental therapy; i.e., somatostatin analogues, dopamine-D2-agonists, the combination of somatostatin analogues and dopamine-D2-agonists. 26 Future studies will elucidate the effects of selective somatostatin analogues 29,30 and BIM 31,32 on α-subunit, gonadotropins, and tumour size. Temozolomide therapy for resistant pituitary adenomas including NFPAs 12 is a new experimental therapy, where monitoring of αsubunit and gonadotropins may be of value.…”
Section: Discussionmentioning
confidence: 99%